2021
DOI: 10.1136/bmjopen-2020-042862
|View full text |Cite
|
Sign up to set email alerts
|

Surgical care in district hospitals in sub-Saharan Africa: a scoping review

Abstract: ObjectiveTo provide a general overview of the reported current surgical capacity and delivery in order to advance current knowledge and suggest targets for further development and research within the region of sub-Saharan Africa.DesignScoping review.SettingDistrict hospitals in sub-Saharan Africa.Data sourcesPubMed and Ovid EMBASE from January 2000 to December 2019.Study selectionStudies were included if they contained information about types of surgical procedures performed, number of operations per year, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 57 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…There is significant shortage in surgical workforce which is below the standard set for district level surgical service provision. These relates with studies done in sub-Saharan countries having difficulty to fulfill 20 surgical workforce per 100,000 population [8] .…”
Section: Discussionmentioning
confidence: 96%
“…There is significant shortage in surgical workforce which is below the standard set for district level surgical service provision. These relates with studies done in sub-Saharan countries having difficulty to fulfill 20 surgical workforce per 100,000 population [8] .…”
Section: Discussionmentioning
confidence: 96%
“…While we did not measure time to care, other studies have demonstrated DH surgical care to be more timely than transfer to tertiary hospitals. [18] Secondly, it offloads the trauma burden that would otherwise be treated at the tertiary hospital, which is often overburdened with long waiting lists for complex and elective orthopaedic operations. KDH therefore plays a massive role in releasing this bottleneck, strengthening district trauma services, and delivering definitive orthopaedic care.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed/MEDLINE, EMBASE, CINAHL, Web of Science, and Google Scholar were searched from January 2010 to November 2022 for completed studies that reported the incidence and risk factors of postoperative complications among patients undergoing Emergency & essential surgery in SSA. The year 2010 marked a pivotal period where significant attention was drawn to the burden of surgical disease in sub-Saharan Africa, as highlighted in existing literature ( 13 ). Additional studies were searched manually from reference lists of some important articles.…”
Section: Methodsmentioning
confidence: 99%